Feeding different proteic level diets to Apis mellifera hives attacked by Varroa jacobsoni - Couto, Leomam Almeida; Couto, Regina Helena Nogueira (Pesquisa Agropecuaria Brasileira, 2014)
Apis mellifera hives were fed diets containing corn gluten/corn meal with 40%, 30% and 20% crude protein. The ration with corn gluten/corn meal with 30% crude protein was preferred and during the experimental period, there was an increase in honey stores and a decrease in the rate of infestation by Varroa jacobsoni. This variation seams to be related with the quantities of feed present in the region during the seasons (February-June) in which these experiments was realized and of the climate conditions too.